Inside the presidential debates their improbable past and promising future - Minow, Newton N., 1926-; LaMay, Craig L. (Chicago University of Chicago Press, 2008)
This fascinating history offers, for the first time, a genuinely informative inside look into the origins of the presidential debates and the many battles--both legal and personal--that have determined who has been allowed to debate and under what circumstances.
Foreword / Varton Gregorian -- Acknowledgments -- Introduction -- How Adlai Stevenson put John F. Kennedy in the White House -- Presidential debates and "equal opportunity" -- "If you're thirty-two points behind, what else are you going to do?" -- The Commission on Presidential Debates and its critics -- The dilemma : who debates? -- How to improve the presidential debates -- Appendixes -- A. Memorandum of understanding between the Bush and Kerry campaigns, 2004 -- B. Negotiated agreements between the League of Women Voters and the Ford and Carter campaigns, 1976 -- C. Section 312 of the Communications Act : "Reasonable Access" for candidates for Federal Office -- D. Challenges to the CPD under Federal Election and Tax Law -- E. Broadcast debates and the First Amendment -- F. The televised presidential debates, 1960-2004 -- Notes -- Index
Includes bibliographical references (pages [165]-201) and index
Donated by Logan Wangsgard (Hall's Book Drive) Dec. 2015.
Keywords: Presidents -- United States -- Election; Campaign debates -- United States; Television in politics -- United States; United States -- Politics and government -- 1945-1989.; United States -- Politics and government -- 1989-